Quantitative multi-omics analysis of the effects of mitochondrial dysfunction on lipid metabolism in Saccharomyces cerevisiae - Guo, Xiaopeng; Zhang, Miaomiao; Gao, Yue; Cao, Guozhen; Lu, Dong; Li, Wenjian (Applied microbiology and biotechnology, 2020)
In this study, combined genome, transcriptome, and metabolome analysis was performed for eight Saccharomyces cerevisiae mitochondrial respiration-deficient mutants. Each mutant exhibited a unique nuclear genome mutation pattern; the nuclear genome mutations, and thus potentially affected genes and metabolic pathways, showed a co-occurrence frequency of ≤ 3 among the eight mutants. For example, only a lipid metabolism-related pathway was likely to be affected by the nuclear genome mutations in one of the mutants. However, large deletions in the mitochondrial genome were the shared characteristic among the eight mutants. At the transcriptomic level, lipid metabolism was the most significantly enriched Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway for differentially expressed genes (DEGs) co-occurring in both ≥ 4 and ≥ 5 mutants. Any identified DEG enriched in lipid metabolism showed the same up-/down-regulated pattern among nearly all eight mutants. Further, 126 differentially expressed lipid species (DELS) were identified, which also showed the same up-/down-regulated pattern among nearly all investigated mutants. It was conservatively demonstrated that the similar change pattern of lipid metabolism in the entire investigated mutant population was attributed to mitochondrial dysfunction. The change spectrum of lipid species was presented, suggesting that the number and change degree of up-regulated lipid species were higher than those of down-regulated lipid species. Additionally, energy storage lipids increased in content and plasma-membrane phospholipid compositions varied in the relative proposition. The results for the genome, transcriptome, and lipidome were mutually validated, which provides quantitative data revealing the roles of mitochondria from a global cellular perspective.